Efektivitas Model Konseling Behavioral dengan Menggunakan Teknik Self Management untuk Meminimalisir Perilaku Fanatisme terhadap Tokoh Idola - Dinda Aulia Putri Rosanty; Fitria Kasih; Rahma Wira Nita (Jurnal Counseling Care, 2023)
This research is motivated by students who exhibit fanaticism behavior towards their idol figure. The purpose of the research is to describe: 1) the fanaticism behavior towards the idol figure of the students before receiving behavioral counseling services using self-management techniques. 2) the fanaticism behavior towards the idol figure of the students after receiving behavioral counseling services using self-management techniques. 3) the effectiveness of the behavioral counseling model using self-management techniques to minimize the fanaticism behavior towards the idol figure of the students.the type of this research is experimental research method. Population of this research is 3 students. Sampling of thes research is using purposive sampling technique.the results of the study reveal that: 1) the fanaticism behavior towards the idol figure of the students before receiving behavioral counseling services using self-management techniques is categorized as high, with a percentage of 33.33% in the high criteria and 66.67% in the very high criteria. 2) the fanaticism behavior towards the idol figure of the students after receiving behavioral counseling services using self-management techniques is categorized as very low, with a percentage of 33.33% in the very low criteria and 66.67% in the low criteria. 3) there is an effectiveness of implementing behavioral counseling services using self-management techniques to minimize the fanaticism behavior towards the idol figure of the students. Keywords: Behavioral Counseling, Self Management Techniques, Fanaticism, Idol Figures.